The EphA8 Receptor Regulates Integrin Activity through p110γ Phosphatidylinositol-3 Kinase in a Tyrosine Kinase Activity-Independent Manner - Gu, Changkyu (American Society for Microbiology, 2001)
Recent genetic studies suggest that ephrins may function in a kinase-independent Eph receptor pathway. Here we report that expression of EphA8 in either NIH 3T3 or HEK293 cells enhanced cell adhesion to fibronectin via α(5)β(1)- or β(3) integrins. Interestingly, a kinase-inactive EphA8 mutant also markedly promoted cell attachment to fibronectin in these cell lines. Using a panel of EphA8 point mutants, we have demonstrated that EphA8 kinase activity does not correlate with its ability to promote cell attachment to fibronectin. Analysis using EphA8 extracellular and intracellular domain mutants has revealed that enhanced cell adhesion is dependent on ephrin A binding to the extracellular domain and the juxtamembrane segment of the cytoplasmic domain of the receptor. EphA8-promoted adhesion was efficiently inhibited by wortmannin, a phosphatidylinositol 3-kinase (PI 3-kinase) inhibitor. Additionally, we found that EphA8 had associated PI 3-kinase activity and that the p110γ isoform of PI 3-kinase is associated with EphA8. In vitro binding experiments revealed that the EphA8 juxtamembrane segment was sufficient for the formation of a stable complex with p110γ. Similar results were obtained in assay using cells stripped of endogenous ephrin A ligands by treatment with preclustered ephrin A5-Fc proteins. In addition, a membrane-targeted lipid kinase-inactive p110γ mutant was demonstrated to stably associate with EphA8 and suppress EphA8-promoted cell adhesion to fibronectin. Taken together, these results suggest the presence of a novel mechanism by which the EphA8 receptor localizes p110γ PI 3-kinase to the plasma membrane in a tyrosine kinase-independent fashion, thereby allowing access to lipid substrates to enable the signals required for integrin-mediated cell adhesion.